A tale of two stories: COVID-19 and disability. A critical scoping review of the literature on the effects of the pandemic among athletes with disabilities and para-athletes - Puce, Luca; Trabelsi, Khaled; Ammar, Achraf; Jabbour, Georges; Marinelli, Lucio; Mori, Laura; Kong, Jude Dzevela; Tsigalou, Christina; Cotellessa, Filippo; Schenone, Cristina; Samanipour, Mohammad Hossein; Biz, Carlo; et al. (Frontiers in Physiology, 2022)
The still ongoing COVID-19 pandemic has dramatically impacted athletes, and, in particular, para-athletes and athletes with disabilities. However, there is no systematic scholarly appraisal on this topic. Therefore, a critical systematic scoping review of the literature was conducted. We were able to retrieve fifteen relevant studies. The sample size ranged from 4 to 180. Most studies were observational, cross-sectional, and questionnaire-based surveys, two studies were interventional, and two were longitudinal. One study was a technical feasibility study. Almost all studies were conducted as single-country studies, with the exception of one multi-country investigation. Five major topics/themes could be identified: namely, i) impact of COVID-19-induced confinement on training and lifestyles in disabled athletes/para-athletes; ii) impact of COVID-19-induced confinement on mental health in disabled athletes/para-athletes; iii) impact of COVID-19-induced confinement on performance outcomes in disabled athletes/para-athletes; iv) risk of contracting COVID-19 among disabled athletes/para-athletes; and, finally, v) impact of COVID-19 infection on disabled athletes/para-athletes. The scholarly literature assessed was highly heterogeneous, with contrasting findings, and various methodological limitations. Based on our considerations, we recommend that standardized, reliable tools should be utilized and new, ad hoc questionnaires could be created, tested, and validated. High-quality, multi-center, cross-countries, longitudinal surveys should be conducted to overcome current shortcomings. Involving all relevant actors and stakeholders, including various national and international Paralympic Committees, as a few studies have done, is fundamental: community-led, participatory research can help identify gaps in the current knowledge about sports-related practices among the disabled athlete population during an unprecedented period of measures undertaken that have significantly affected everyday life. Moreover, this could advance the field, by capturing the needs of para-athletes and athletes with disabilities and enabling the design of a truly "disability-inclusive response” to COVID-19 and similar future conditions/situations. Furthermore, follow-up studies on COVID-19-infected para-athletes and disabled athletes should be conducted. Evidence of long-term effects of COVID-19 is available only for able-bodied athletes, for whom cardiorespiratory residual alterations and mental health issues a long time after COVID-19 have been often described.